Analysis of the Fixed Oil from the Stem of Crotalaria verrucosa - Yadava, R.N.; R. Mathews, Sunu. (Asian Journal of Chemistry, 2010)
In the present work, the authors have analysed the fixed oil extracted from the stem of Crotalaria Verrucosa.